2007
DOI: 10.1097/01.mat.0000247155.20214.20
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Heparin on Lipid Parameters in Patients on Renal Replacement Therapy

Abstract: Dialyzer membrane and the type of heparin used can influence lipid parameters. However, there are limited and debatable data concerning lipid alterations during a single hemodialysis session. Moreover, the role of hemoconcentration after every hemodialysis session confuses the real effect of the heparin on lipid profile. We investigated the acute effect of heparin administration on lipids in hemodialysis patients, but on an off-hemodialysis day in order to eliminate any effect of ultrafiltration. We studied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…This early phase of high LPL activity in the circulating blood is reflected by decreased levels of TG [5,19,20]. In agreement with Akiba et al [21] and Katopodis et al [19] we found that this early fall of plasma TG was less marked with the LMW-heparin than with the UF-heparin. There was a similar trend in the earlier study by Näsström et al [5] but in that case the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This early phase of high LPL activity in the circulating blood is reflected by decreased levels of TG [5,19,20]. In agreement with Akiba et al [21] and Katopodis et al [19] we found that this early fall of plasma TG was less marked with the LMW-heparin than with the UF-heparin. There was a similar trend in the earlier study by Näsström et al [5] but in that case the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…Only a fraction of the lipoprotein particles are "marginated" at the endothelium, in contact with LPL [18]. This early phase of high LPL activity in the circulating blood is reflected by decreased levels of TG [5,19,20]. In agreement with Akiba et al [21] and Katopodis et al [19] we found that this early fall of plasma TG was less marked with the LMW-heparin than with the UF-heparin.…”
Section: Discussionsupporting
confidence: 88%
“…Another study by Katopodis et al [8] has shown that a reduction in TG levels in first, second and third hour administration of unfractionated IV heparin in patient on renal replacement therapy. Although the aforementioned studies determined the effect of administered heparin by on lipid TG, this study used in vitro heparin anticoagulant tube.…”
Section: Discussionmentioning
confidence: 94%
“…Based on this information hemodialysis seems to have a powerful capacity for modifying the lipid pro ile, inducing hepatic secretion of LDL and increasing the amount of cholesterol mobilized by HDL. Therefore, hemoconcentration is not the only factor responsible for lipid pro ile changes [19].…”
Section: Discussionmentioning
confidence: 99%